1995
DOI: 10.1002/masy.19950990122
|View full text |Cite
|
Sign up to set email alerts
|

Novel polymeric excipients for colon‐targeting

Abstract: Oral drug delivery to the colon is of interest for the local treatment of colonic diseases and for the systemic delivery of drugs. Our goal is to develop coating materials that are stable in gastric and small intestinal fluids and degradable in the colon by bacterial polysaccharidases. For testing colon‐degradability an in vitro model was developed. A number of polysaccharide derivatives were synthesized and tested: almost completely ethylated or acetylated galactomannans, polyurethanes with galactomannan sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results of both studies showed that this coating was able to protect the drug from being released in the stomach and small intestine, but was degraded by colonic bacterial enzymes (Raghavan et al, 2002). The galactomannans in locust bean gum can be cross-linked, forming a water-insoluble film, which can then be degraded by bacteria in the colon (Hirsch et al, 1995). Locust bean gum galactomannans were crosslinked by 1,4-butanedioldiglycidyl ether, yielding a low crosslinked product that can be used to form films.…”
Section: Galactomannan-containing Gumsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of both studies showed that this coating was able to protect the drug from being released in the stomach and small intestine, but was degraded by colonic bacterial enzymes (Raghavan et al, 2002). The galactomannans in locust bean gum can be cross-linked, forming a water-insoluble film, which can then be degraded by bacteria in the colon (Hirsch et al, 1995). Locust bean gum galactomannans were crosslinked by 1,4-butanedioldiglycidyl ether, yielding a low crosslinked product that can be used to form films.…”
Section: Galactomannan-containing Gumsmentioning
confidence: 99%
“…The material was then used to spraycoat theophylline tablets, which were used as a model drug. When placed under conditions representing passage through the small intestine, drug release was observed, but the researchers concluded that the lag time prior to drug release could be increased by applying a thicker coating of the crosslinked galactomannans (Hirsch et al, 1995).…”
Section: Galactomannan-containing Gumsmentioning
confidence: 99%